Episcleritis Uncovered: A Thorough Review of Current Research - Błaszczak, Ewa; Wójcik, Jakub; Dydyk, Martyna; Małachowski, Aleksander; Malinowski, Piotr; Kopczyńska, Urszula; Kopczyński, Cezary; Gurdak, Kinga; Dyrek, Martyna; Partyka, Aleksandra (Journal of Education, Health and Sport, 2024)
Episcleritis is an inflammatory condition affecting the episclera of the eye, which is the tissue between the sclera and conjunctiva. It manifests as unilateral or bilateral redness and discomfort. Despite its typically benign course, it may signal underlying systemic disorders, necessitating comprehensive evaluation and personalized management. While most cases are idiopathic, autoimmune diseases and infections may play contributory roles. Epidemiological studies reveal a predilection for young to middle-aged females, with episcleritis being less common in children. Diagnostically, characteristic features include sectoral redness and mild discomfort, distinguishing it from conjunctivitis and scleritis. Treatment primarily focuses on symptomatic relief, utilizing topical steroids, oral NSAIDs, and artificial tears. The prognosis is generally favourable, with spontaneous resolution within weeks; however, recurrent, or chronic cases may necessitate further evaluation for underlying systemic conditions. This comprehensive review aims to elucidate etiology, epidemiology, diagnosis, management strategies, prognosis of episcleritis, and clinical nuances, drawing upon recent literature from 1976 to the present. By consolidating contemporary knowledge, this review provides valuable insights for clinicians on how to treat this ocular condition effectively.